الكوميديا السوداء في قصص يوسف إدريس - شافعي أمال (My University, 2025)
This study undertakes a critical examination of the manifestations of black comedy in the short stories of Youssef Idriss, with a specific focus on three narratives: A Tray Fallen from the Sky, The Black Soldiers, and A House of Flesh. The research begins by establishing a theoretical framework that defines the concept of black comedy, delineating its aesthetic and thematic characteristics as well as its principal expressions in both Western and Arab literary traditions. Building upon this foundation, the study offers an in-depth literary analysis of the selected texts, demonstrating how Idriss strategically employs irony, paradox, and dark satire as artistic devices to expose and critique the social, political, and existential conditions of his time. The findings reveal that black comedy in Idriss’s oeuvre functions not merely as an aesthetic mode but also as a form of intellectual and ethical engagement one that reflects a profound awareness of human tragedy and a boldness in addressing taboo or contentious issues. Through this approach, Idriss endows his narratives with significant philosophical depth and a distinctive artistic resonance ------------------------- ملخص: تناولنا في هذه المذكرة بالدراسة والتحليل مظاهر الكوميديا السوداء، في قصص يوسف إدريس، مركزين على ثلاث نماذج سردية، طبلية من السماء، العسكر الأسود وبيت من لحم. وقد انطلقت الدراسة من تأطير نظري يعرف الكوميديا السوداء ويبين قصائصها وأهم تمثلاتها في السياقين الغربي والعربي، لتنتقل بعدها إلى تحليل فني دقيق للقصص المختارة، مبينة كيف استخدم يوسف إدريس التهكم والمفارقة والسخرية السوداء كأدوات فنية لنقد الواقع الاجتماعي والسياسي والإنساني، وقد خلصت الدراسة إلى أن الكوميديا السوداء في أعمال إدريس ليست شكلاً جمالياً فحسب، بل هي خطاب واع يعكس واعياً حاداً بالمأساة وجرأة في الطرح، ما يمنح نصوصه عمقاً إنسانياً وفنياً لافتاً. ------------------- Résumé : Dans ce mémoire, nous avons étudié et analysé les manifestations de la comédie noire dans les nouvelles de Youssef Idriss, en nous concentrant sur trois récits narratifs : Un plateau tombé du ciel, Les soldats noirs et Une maison de chair. L'étude a débuté par un cadre théorique définissant la comédie noire, en exposant ses caractéristiques et ses principales représentations dans les contextes occidental et arabe. Elle s'est ensuite poursuivie par une analyse artistique approfondie des nouvelles choisies, mettant en lumière la manière dont Youssef Idriss utilise l'ironie, le paradoxe et la satire noire comme outils esthétiques pour critiquer la réalité sociale, politique et humaine. L'étude conclut que la comédie noire dans les œuvres d’Idriss ne constitue pas seulement une forme esthétique, mais représente également un discours conscient, reflet d’une perception aiguë de la tragédie et d’une audace dans le traitement des sujets, ce qui confère à ses textes une profondeur humaine et artistique remarquable
Keywords: القصة، الكومديا السوداء، بيت من لحم، طبلية من السماء، العسكري الأسود.